Visualisasi Branding Kemasan Olahan Ikan sebagai Daya Tarik dan Informasi Usaha Mikro Sari Mina Segara - Dewi, Putu Julyantika Nica; Kinasih, Mentari; Purnamawati, Ida Ayu Putu Santi; Saraswati, I Gusti Ayu Krisma Widya; Premanayasa, I Wayan Gede Andhika; Yudhistira, Dewa Made Raditya Dwi; Purnamasari, I Gusti Ayu Agung Jaya (Universitas Prof. Dr. Moestopo (Beragama), 2026)
This community service program with the Sari Mina Segara Group in Sangsit Village aimed to improve the competitiveness of Sudang Lepet and other fish-based products facing issues of short shelf life, simple packaging, and also limited marketing. The program introduced vacuum packaging, standardized labeling, and digital marketing strategies. Implementation involved training, mentoring, and equipment assistance. The results showed vacuum packaging extended shelf life, enhanced product safety, and reduced contamination risks. Informative labeling combined with Balinese cultural elements strengthened brand identity and consumer appeal. Digital marketing aspect has expanded product reach beyond local markets, improving sales, and visibility. Initial resistance to make a new technology was overcome through step-by-step guidance, leading to full participation and independent management of packaging and promotion. Overall, the program helps to strengthened product quality, broadened market access, and supported business sustainability in line with SDGs 8 and 12. Replication for other fisheries-based MSMEs is recommended to enhance competitiveness and eco-friendly packaging innovation.